Nationalism and Racism - Yuval-Davis, Nira (Cahiers de recherche sociologique, 1993)
SummaryThis article propose a typology of the ideologies underwriting nationalist projects and seeks to show that ethnic divisions, based on "race" and nation, do not constitute mutually exclusive categories. It distinguishes between nationalisms predicated on biological origin, culture, and religion. It follows with a discussion of nationalism based on the ideologies of multiculturalism or cultural pluralism. Finally, it treats the themes of nationalism and citizenship, arguing that in western nation-states constructed around a universalist notion of citizenship, issues pertaining to immigration and racism serve to delineate the borders of citizenship.